S82 Survival of HIV-infected patients admitted to the intensive care unit. (16th November 2010) - Adlakha, A G; Pavlou, M; Walker, D; Copas, A J; Batson, S; Edwards, S G; Singer, M; Miller, R F
Abstract : Background: Several studies from USA and Europe have suggested the outcome for HIV-infected patients admitted to the intensive care unit (ICU) has improved, concurrent with both the introduction of highly active antiretroviral therapy (HAART) and improved management of respiratory failure. This study examined outcomes and prognostic factors for HIV-infected patients admitted to our ICU over a 10-year period. Methods: Retrospective study of HIV-infected adults admitted to a UK University-affiliated hospital ICU between January 1999 and March 2009. Information collected included patient demographics, receipt of HAART (no patient began HAART while on the ICU), reason for ICU admission and hospital course. Outcomes were survival to ICU and hospital discharge. Comparison was made against outcomes for general medical patients admitted to the same ICU. Multivariate analysis was used to assess prognostic factors. Results: 192 HIV-infected patients had 222 admissions to the ICU. Among these 192 patients, 116 required mechanical ventilation and 43 renal replacement therapy. Their ICU admission was due to an HIV-associated diagnosis in 113 patients; 37 patients had Pneumocystis pneumonia. Survival to ICU discharge and hospital discharge was 78% and 70%, respectively, compared with 75% and 68% among 2065 general medical patients admitted to the ICU on 2274 occasions over the same time period. HIV infection was newly diagnosed (on this hospital admission) in 42 patients; among this group ICU and hospital survival was 69% and 57%, respectively. Factors associated with ICU survival were age (OR=0.97, 95%CI 0.93 to 1.00, per 10 year increase), haemoglobin (OR=1.33, 95%CI 1.07 to 1.65, for an increase of 1 g/dl), APACHE II score (OR=0.56, 95%CI 0.39 to 0.90, per 10 unit increase), receipt of HAART (OR=2.88, 95%CI 1.29 to 6.42) and need for mechanical ventilation (OR=0.18, 95%CI 0.07 to 0.43). Conclusions: In the era of HAART the outcome from ICU for HIV-infected patients was comparable to that among general medical patients. These data infer neither HIV infection itself, nor an HIV-associated diagnosis should preclude referral to the ICU. The poorer outcome among those with newly diagnosed HIV infection underscores the need to encourage HIV testing outside of Genitourinary Medicine clinics.